QUANTIFICATION OF THE CATEGORIES OF DROSOPHILAS AND YEAST BY THE METHODS OF RECIPROCAL AVERAGES AND VARIANCE ANALYSIS - Gómez Ticerán, Doris (2010)
A latent problem in two-dimensional contingency tables is to quantify the levels of categorical variables involved. In this paper we choose the nonlinear multivariate descriptive methods, Reciprocal averaging method and Variance Analysis method for quantifying levels of drosophilas and yeast, categorical variables of twodimensional contingency table. The results show that it was possible to quantify the categories drosophilas and yeast by the methods mentioned, the same ones that produce different quantifications of the categories traditionally used for the rows and columns of the contingency table.